Electrodeposition of platinum metals and alloys from chloride melts - Saltykova N.A. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The structure of platinum metals and their alloys deposited by the electrolysis of chloride melts have been investigated. The cathodic deposits were both in the form of compact layers and dendrites. All the alloys of platinum metals obtained are solid solutions in the whole range of composition. Depending on the experimental conditions the layers had columnar, stratum and spiral (dissipative) structures. The stratum and dissipative structures were observed in the case of alloys only.